Oral and faecal microbiota in volunteers with hypertension in a double blind, randomised placebo controlled trial with probiotics and fermented bilberries. (October 2015) - Xu, Jie; Lazou Ahrén, Irini; Olsson, Crister; Jeppsson, Bengt; Ahrné, Siv; Molin, Göran
Highlights: 3 month-intake of DSM 15313 or its fermented bilberries had no effect on hypertension. The studied products did not significantly affect the oral and the faecal microbiota. The gut microbiota was highly stable in the studied hypertensive adults. The oral microbiota showed more fluctuation and larger variation between individuals. Abstract: Two probiotic products containing either live Lactobacillus plantarum strain DSM 15313 or bilberries fermented by the same bacterial strain were tested for their antihypertensive potentials and their impact on the oral and the faecal microbiota in hypertensive adults. The results showed that consumption of the tested products for three months did not reduce the blood pressure in adults with hypertension. Neither the diversity nor the composition of the oral and faecal microbiota was significantly affected by the tested probiotic products. Moreover, the oral and the faecal microbiota remained generally stable over the intervention period of 3 months.